Obnašanje stika med betonom in armaturnimi palicami iz bazaltnih vlaken - Saje, Drago (Gradbeni vestnik, 2021)
The article discusses the behaviour of anchorage of basalt fibre reinforcement bars in concrete. As a non-metallic reinforcement, basalt reinforcement has many advantages over steel. The main advantage of basalt reinforcement is that it does not corrode and is therefore suitable for use in aggressive environments. Some other advantages, disadvantages and peculiarities in fabrication, regulation and application of this reinforcement in practice are mentioned in the introductory section. Basalt reinforcement is one of the newest among fibre reinforced polymer reinforcements, which are already being used in practice and therefore still require intensive research in many areas. The results of bond behaviour studies are the basis for determining the required anchorage and lap lengths of reinforcing bars. We started to investigate the bond behaviour between basalt rebars and concrete with pull-out tests years ago Saje, 2019. In this process, we monitor the bond stress and slip of the bars and determine the bond strength. The article presents the results of the bond behaviour of basalt reinforcing bars with a diameter of 12mm and two types of concrete, normal strength concrete and high strength concrete. Thebasalt reinforcement bars were helically wrapped and sand coated. For comparison, the results of pull-out tests with ribbed steel reinforcement of the same diameter in both types of concrete are also presented. It was found that the specimens with basalt reinforcement achieved about 70% of the bond strength of specimens with steel reinforcement. However, it was also found that for both basalt and steel reinforced specimens, the compressive strength of the concrete has a great influence on the bond strength and on the relationship between the bond stress and the measured slip.
Keywords: basalt rebars; bazaltna armatura; beton; bond strength; high strength concrete; izvlečni test; jeklena armatura; pull-out test; slip; sprijemna trdnost; steel rebars; zdrs